Highway toll allocation - Hao Wu; Rene van den Brink; Arantza Estevez-Fernandez (Tinbergen Institute, 2022)
This paper analyzes the allocation of the total toll collected in a highway among its segments. Based on different toll charging rules, we propose the Segments Equal Sharing method, the Exits Equal Sharing method, and the Entrances Equal Sharing method. We provide axioms and characterize these methods used to distribute the toll. Besides, we show how these methods can be obtained by applying the Shapley value to associated coalitional transferable utility games.
Keywords: R49; C71; 330; Highway toll allocation problem; Axiomatic characterization; Shapley value